The management of Asherman syndrome in gynecology (Faculty of Medicine Universitas Indonesia, 2013)
Asherman syndrome is an acquired condition characterized by the formation of adhesions in the uterine cavity. This condition is often caused by trauma to the endometrium, which mostly happens after currettage or post-partum, and can produce several complications such as menstrual disturbances, infertility, or recurrent abortion. The management of Asherman syndrome requires complete actions which can be summarized with the acronym PRACTICE, consisting of prevention, anticipation, comprehensive therapy, timely surveillance of subsequent pregnancies, investigation and continuing education. The prevention and anticipation aspects can be performed through reduction of invasive methods of therapy such as currettage, prophylactic therapy for adhesions such as antibiotics and post-estrogen therapy for high risk patients, and the use of instruments that do less damage to the uterine walls. The comprehensive therapy that become the method of choice is operative lysis using hysteroscopy, which provides direct visualization of the adhesion. To prevent reccurrence, especially to patients planning to have subsequent pregnancies, timely surveillance of the next pregnancies for high risk patients should be performed at hospital, with complete work-ups. Lastly, evaluation of operative results and continuing education to explain prognoses to the patient should be also performed. (Med J Indones. 2013;22:121-6)